PEMILIHAN SEKOLAH TERBAIK DENGAN MENGGUNAKAN METODE K-NEAREST NEIGHBORS DAN TAXONOMIC MATCHER - Bidari Ayu Lestari; Muhammad Hasbi; Teguh Susyanto (STMIK Sinar Nusantara, 2018)
The accuracy of choosing the right school is what every prospective student and parent wants. But in making the decision to choose the right school is not easy to do, because many aspects that are not simple must be taken into account. Mistakes in making decisions for prospective students must risk the loss of opportunities. Calculations in choosing a prospective student must be able to measure rationally the level of ability themselves with the quality of the school to be chosen. The quality of the school is determined based on the school's favorite level, the value of school accreditation, facilities owned, and achievements that have been achieved by the destination school. The purpose of this study was to apply the K-Nearest Neighbors (KNN) and Taxonomic Matcher methods to the creation of a system for selecting schools. The results of the development of the school selection application have been running in accordance with its functions and the results of the user acceptance test have been approved because it has a higher value than the answer agreed on the Likert scale which is 4.188571 on a scale of 1-5.Keywords: K-Nearest Neighbors (KNN), Taxonomic Matcher, Choosing a School